HUBUNGAN PERILAKU PICKY EATER DAN DURASI TIDUR DENGAN PERKEMBANGAN PADA BALITA - Salsabila Ratyana Putri; Fransisca Chondro (Jurnal Akta Trimedika, 2024)
In toddlerhood, children begin to understand the concept of autonomy so they start to choose things they like, one of which is the behavior of choosing food, namely picky eaters. If the nutritional intake is less varied, there’s a possibility that the child won’t get sufficient nutrition that support the development process. In addition to nutritional intake, responsive parenting is essential in meeting children's needs, such as adequate sleep time. Sleep in children facilitates the maturation and repair of body cell functions, including brain cells and hormones that play a role in development. This study used a cross-sectional study design using primary data from 138 toddlers in the Posyandu of Tanjung Duren Utara Village. Assessment of picky eater behavior using the Children’s Eating Behavior Questionnaire (CEBQ), sleep duration using the average questionnaire of sleep duration and child development using the Indonesian pre-screening developmental questionnaire, Kuesioner Pra-Skrining Perkembangan (KPSP). Analysis of bivariate data using the Chi-square test with a significance level of p<0.05. Among the 138 respondents, it was found that the majority had picky eater behavior, namely 93 (67.4%) children, 73.2% children have an adequate sleep duration, and 57.2% children have  appropriate development. The relationship between picky eater behavior and development through statistical tests obtained a p = 0.035 (p <0.05) and between sleep duration and development p=0.298 (p>0.05). There is a relationship between picky eater behavior and development in toddlers and no relationship between sleep duration and results in toddlers.